Pengetahuan Siswa Kelas IV Tentang Makanan Kariogenik di SDN Kertajaya I Surabaya - Ana Setiowati; Silvia Prasetyowati; Agus Marjianto (Poltekkes Kemenkes Surabaya, 2024)
Background: Cariogenic foods are foods that contain lots of sugar, are sweet, sticky and easily disintegrate in the oral cavity. This sweet and sticky food is generally very popular with school-age children because of its delicious taste, attractive shape and low price. Objective: This study aims to describe the knowledge of class IV students about cariogenic food at SDN Kertajaya 1 Surabaya in 2023. Method: this type of research is descriptive research. The target in this study was 39 grade IV students for the 2022/2023 academic year. The data collection method was obtained by using a questionnaire sheet. The data analysis technique used is to count the number of correct answers and then calculate the average and present it in tabular form. Results: The knowledge of fourth grade students at SDN Kertajaya 1 Surabaya about the meaning of cariogenic food is in the good category. Students' knowledge of the types or types of cariogenic food has moderate criteria. Student's knowledge of students' knowledge about the time of cariogenic food has less impact or effect of cariogenic food has good criteria. Conclusion: fourth grade students' knowledge of cariogenic food at SDN Kertajaya 1 Surabaya in 2023 is in the moderate category